Comparative expression analysis of embryonic development-related genes at different stages of parthenogenetic and in vitro fertilized embryos in caprine. Issue 2 (30th October 2013) - Singh, Renu; Kumar, Kuldeep; Ranjan, R.; Kumar, Manish; Yasotha, T.; Singh, R.K.; Das, B.C.; Sarkar, M.; Bag, Sadhan
Summary: Aberrant gene expression occurs in parthenogenetic embryos due to abnormal epigenetic modifications in the genome that probably diminish viability and enhance developmental abnormalities in these embryos. In the present study, five developmentally important genes ( HPRT1, Cx43, Sox2, Mest and IGF2R ) were analysed at different stages in parthenotes (haploid and diploid) and compared with similar stages in in vitro fertilized (IVF) embryos. The results indicated that in haploid parthenotes expression of HPRT1 was upregulated ( P < 0.05) only at the 2–4-cell stage whereas Cx43 expression was significantly ( P < 0.05) downregulated in all stages as compared with the control. However, expression of this gene was upregulated ( P < 0.05) in 2–4-cell and morula stages of diploid parthenotes. Expression of Sox2 was significantly ( P < 0.05) downregulated in morula stage haploid parthenotes, whereas it was upregulated ( P < 0.05) in 8–16-cell stage diploid embryos. The expression of Mest was upregulated ( P < 0.05) at the 2–4-cell stage of both haploid and diploid parthenotes, whereas it was downregulated in 8–16-cell stage diploid embryos as compared with control. IGF2R expression was upregulated ( P < 0.05) only in morula stage haploid and diploid parthenote as compared with control. These results indicate that parthenogenetic embryos showed aberrant gene expression of developmentally important genes such as HPRT1, Cx43, Sox2, Mest and IGF2R in comparison with IVF embryos, this finding may be one of the major reasons for the poor developmental competence of parthenogenetic embryos.